(3efM GdeOMs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s
(3ChdgG (B:s
(3bGd GdTjN HYO MeOGddg GdPi YeJ BdGDg adeG hVYJ cJGHi GdeSei s
(3BNQgG (B:s
(3hbO GTJedJ GdbUjI Ydi bQjHef eFg hJSYjf ef UMGHi hUMGHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3fSNI KGfjIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi EdG ai jSjQ ef GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B113 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs